Differentiation enhances aminolevulinic acid-dependent photodynamic treatment of LNCaP prostate cancer cells - Ortel, B (Nature Publishing Group, 2002)
Photodynamic therapy using 5-aminolevulinic acid (ALA)-induced protoporphyrin IX (PpIX) may be applied to the treatment of neoplasms in a variety of organs. In order to enhance existing regimens of photodynamic therapy, we investigated the effects of adding differentiation therapy to photodynamic therapy in human prostate cancer cells in vitro. The objective of differentiation therapy per se is to reverse the lack of differentiation in cancer cells using pharmacological agents. The motivation for this study was to exploit the differentiation-dependent expression of some heme enzymes to enhance tumour cell toxicity of ALA-photodynamic therapy. A short course of differentiation therapy was applied to increase PpIX formation during subsequent ALA exposure. Using the synthetic androgen R1881, isomers of retinoic acid, and analogues of vitamin D for 3 to 4 days, exogenous ALA-dependent PpIX formation in LNCaP cells was increased, along with markers for growth arrest and for differentiation. As a consequence of higher PpIX levels, cytotoxic effects of visible light exposure were also enhanced. Short-term differentiation therapy increased not only the overall PpIX production but also reduced that fraction of cells that contained low PpIX levels as demonstrated by flow cytometry and fluorescence microscopy. This study suggests that it will be feasible to develop protocols combining short-term differentiation therapy with photodynamic therapy for enhanced photosensitisation. British Journal of Cancer (2002) 87, 1321–1327. doi:10.1038/sj.bjc.6600575 www.bjcancer.com © 2002 Cancer Research UK